1997
DOI: 10.1038/sj.leu.2400746
|View full text |Cite
|
Sign up to set email alerts
|

Differential CD95 expression and function in T and B lineage acute lymphoblastic leukemia cells

Abstract: recently, several bcl-2-related genes were cloned

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 8 publications
6
37
1
Order By: Relevance
“…Despite the rather low number of TRAIL sensitive leukemic cell samples in this subtype, we found that precursor B cell ALL disclosed a higher in vitro susceptibility to TRAIL-induced apoptosis compared with AML and precursor T cell ALL. This is in contrast to the constitutive susceptibility to CD95(Fas/Apo-1)-induced apoptosis of leukemic cells: precursor B cell ALL cells were significantly less CD95-sensitive compared with precursor T cell ALL and AML cells 34,35,39 Compared with our previous studies on CD95-induced apoptosis in AML and precursor T cell ALL, these subtypes seem to be less sensitive to TRAIL-than to CD95-induced apoptosis. In contrast, precursor B cell ALL samples were rather more susceptible to TRAIL-than to CD95-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Despite the rather low number of TRAIL sensitive leukemic cell samples in this subtype, we found that precursor B cell ALL disclosed a higher in vitro susceptibility to TRAIL-induced apoptosis compared with AML and precursor T cell ALL. This is in contrast to the constitutive susceptibility to CD95(Fas/Apo-1)-induced apoptosis of leukemic cells: precursor B cell ALL cells were significantly less CD95-sensitive compared with precursor T cell ALL and AML cells 34,35,39 Compared with our previous studies on CD95-induced apoptosis in AML and precursor T cell ALL, these subtypes seem to be less sensitive to TRAIL-than to CD95-induced apoptosis. In contrast, precursor B cell ALL samples were rather more susceptible to TRAIL-than to CD95-induced apoptosis.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, precursor B cell ALL samples were rather more susceptible to TRAIL-than to CD95-induced apoptosis. 34,35,39 The independence of CD95 and TRAIL susceptibility is well documented in normal T cells as well as in individual leukemic cell samples. 18,40 To determine whether the expression pattern of TRAIL receptors R1-R4 might explain the rather low TRAIL susceptibility observed, we examined constitutive mRNA levels of these receptors by semi-quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The 48 kDa CD95 surface antigen can mediate apoptosis upon crosslinking with monoclonal antibodies (anti-Fas, anti-APO-1) or natural cognate CD95-L. [7][8][9] Many cell types, both normal and malignant cells, express CD95. [10][11][12][13][14][15] While some T-and B-lineage malignancies are sensitive to CD95 triggering, the majority of primary leukemias are resistant towards CD95-mediated apoptosis. 8,15,16 Triggering of the T cell receptor in peripheral T cells leads to activation-induced cell death via CD95/CD95-L interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] While some T-and B-lineage malignancies are sensitive to CD95 triggering, the majority of primary leukemias are resistant towards CD95-mediated apoptosis. 8,15,16 Triggering of the T cell receptor in peripheral T cells leads to activation-induced cell death via CD95/CD95-L interaction. 17 Similarly, antigen-activation in B cells leads to upregulation of CD95 and sensitivity towards CD95-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%